The Connection between disciplines in the Development of a Training Course - Benussi, Fulvio Oscar; Errico, Anna (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The Digital Social Studies training course was implemented in one Year Four and one Year Five class of the Carlo Tenca High School in Milan in January 2023. The project was carried out by involving a high school teacher in both the design and the teaching. In the design of the training activity, we referred to data from the world of marketing and studies on media education.